IET &Amp; IAM Asset Management Conference 2013 2013
DOI: 10.1049/cp.2013.1945
|View full text |Cite
|
Sign up to set email alerts
|

Information Futureproofing for Large-scale Infrastructure

Abstract: There are challenges of maintaining, refurbishing and modernising infrastructure assets under limited investments available for such purposes. Potential technological and operational challenges exist as a barrier to long-term information retention, which also plays a crucial role, amongst other factors, to futureproof major infrastructure. These issues appear to be trivial for short-term data management where informal information management practices suffice but over a 50+ year timeframe these issues are criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…and then proposed that a dynamic system approach is necessary to deal with change. Masood et al (2013) suggested that "information could also play an important role in supporting whole-life decision-making". In support of the above and following the USA and Krystallis et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and then proposed that a dynamic system approach is necessary to deal with change. Masood et al (2013) suggested that "information could also play an important role in supporting whole-life decision-making". In support of the above and following the USA and Krystallis et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The UK Department of Health (DH, 2013) recognised 13 issues that need to be addressed at each project stage of a healthcare project regarding excellence in sustainability; one of them being future-proofing. Masood et al (2013) defined future-proofing as "the process of incorporating future developments while changing from an unplanned and uncontrolled state to a planned and controlled state of a resilient infrastructure asset or product service system with minimal negative consequences".…”
Section: Introductionmentioning
confidence: 99%
“…Shetty (2014) defined future-proofing in an asset management context as 'the process of anticipating the distant future and taking actions to minimise risks and maximise opportunities for value realisation from assets'. The term 'future-proofing' has also been used for long-term business continuity (ISO, 2012) and long-term information continuity (Masood et al, 2013).…”
Section: What Is Infrastructure Future-proofing?mentioning
confidence: 99%
“…Hence, it is important to identify through-life information requirements at earlier life cycle stages of infrastructure and ensure availability of information at all stages by planning and taking appropriate actions for its collection, retention and reuse in the long term (Masood et al, 2013). The principles outlined here deserve a lot more emphasis due to their importance and should be considered as a criterion for infrastructure future-proofing; however, these are not included in detail as this paper is focused on future-proofing of physical infrastructure.…”
Section: Identify and Contextualise Criteria For Future-proofing Assementioning
confidence: 99%
See 1 more Smart Citation